Characterization of soils in relation to their classification and management for crop production : examples from some areas of the humid tropics - Greenland, D. J. (Oxford : Clarendon Press ; New York : Oxford University Press, 1981)
The book studies the West African soils and the relationship of these properties to their classification and to land use and the influence of climate.
Oxford science publications.
Includes bibliographies and indexes.
occ 17/01/2018
Loans
Keywords: Soils; Soil fertility; Soil management; Land capability for agriculture; Nigeria